Labour Mobility with Vocational Skill: Australian Demand and Pacific Supply - Satish Chand; Michael A. Clemens (Institute of Labor Economics (IZA), 2021)
How many immigrants with less than university education, for a given immigration quota, maximise economic output? The answer is zero in the canonical model of the labour market, where the marginal product of a university-educated immigrant is always higher. We build an alternative model in which national production occurs through a set of Leontief producation functions that shift over time with technological change. This model is used to estimate that the Australian economy growing at historical rates through the year 2050 will demand approximately two million migrant TVET workers, many of which could be supplied from the Pacific Islands.
Keywords: F22; J11; J24; 330; immigration; labor; low skill; TVET; training; human capital; growth